Screening of Hearing Impairment in High-Risk Neonates: A Study at Dr. R.N. Cooper Hospital and H.B.T. Medical College - Panjiyar, Megha Mukund; Bhargava, Samir K; Shetty, Neeraj R; Mhashal, Shashikant; Gite, Vinod (Annals of Otology and Neurotology, 2019)
Introduction The aim of this study was to find out the prevalence of hearing impairment in high-risk neonates born in Dr. R.N. Cooper Hospital and H.B.T Medical College and establish the fact that high-risk neonates have higher prevalence of hearing impairment compared with normal population.Materials and Methods A prospective observational study was conducted over a period of 1 year starting from March 2016 and involved three-stage screening of 410 neonates admitted to neonatal intensive care unit of Dr. R.N. Cooper Municipal General Hospital and H.B.T Medical College, Vile Parle (west), Mumbai. All enrolled neonateswere screened by a three-stage screening mechanism. First otoacoustic emission (OAE-1) screening was done within 24 to 72 hours of birth. Parents of neonates referred by OAE-1 were instructed to come back within 28 days for repeat OAE test (OAE-2). Those referred by OAE-2 were asked to come back after further 2 months for brainstem-evoked response audiometry. Data collected in the study were processed using Microsoft Excel.Results and Conclusion In the current study, out of 410 neonates who were screened by a three-stage screening mechanism, five including three girls and two boys were found to be suffering from profound sensorineural hearing loss. Observed prevalence of 12.20 (or 12 on rounding off to nearest digit) per 1000 in high-risk neonates is much higher compared with the prevalence of 1 to 6 per 1000 live births in overall population as reported by the American Speech-Language-Hearing Association.
Keywords: high-risk neonates; prevalence of hearing impairment; SNHL